Are the effects of work-related extended availability the same for everyone? - Thörel, Eberhard, (Colegio Oficial de Psicólogos de Madrid, 2020)
Work-related extended availability (WREA) describes a state of being available for work matters while physically being in a different life domain. There is ample evidence for the negative effects of WREA, but moderator effects of personal attributes have largely been neglected. The current study examined the impact of neuroticism and segmentation preferences on the relationship between WREA and psychological detachment, sleep problems, and emotional exhaustion. We assumed that WREA would be associated with all three criterion constructs and that these relationships would be moderated by neuroticism and segmentation preferences. These hypotheses were tested with multiple regression and moderated hierarchical regression analysis in a sample of 276 employees. While there was a significant association between WREA and detachment, WREA did not directly predict sleep problems or exhaustion. However, we found an indirect effect of WREA on sleep problems via detachment. Neuroticism and segmentation preferences moderated the association between WREA and exhaustion. While the association between WREA and detachment was robust, WREA predicted emotional exhaustion only for people high in neuroticism or with high segmentation preferences. We suggest that employees who prefer segmenting work and private life should be taken seriously and not be contacted in their leisure time.